Pengaruh Komitmen Organisasional, Kepuasan Kerja Dan Budaya Organisasi Terhadap Kualitas Layanan Pegawai di Dinas Tanaman Pangan Dan Hortikultura Provinsi Sumatera Utara - Rukmini Rukmini; Julaina Nawar; Wan Dian Safina; Toni Hidayat (CERED Indonesia Institute, 2022)
This research activity uses a quantitative research method approach with expost facto type which aims to examine the relationship between phenomena that have occurred either partially or simultaneously. The population of this research is 160 employees with a precision of 5% so that the sample is 114 employees. Based on the results of testing the first hypothesis (H1) partially, the variable organizational commitment has a positive and significant effect on the quality of employee services by 0.021, the results of testing the second hypothesis (H2) partially, the variable job satisfaction has a positive and significant effect on the quality of employee services by 0.023, the results Testing the third hypothesis (H3) partially, the organizational culture variable has a positive and significant effect on the quality of employee services. of 0.000 the results of testing the fourth hypothesis (H4) simultaneously with the F test, the variables of organizational commitment, job satisfaction and organizational culture simultaneously have a positive and significant effect on the quality of employee services together with an effect on the quality of employee services by 25.5% with the multiple regression equation is Y =17.001+0.156 X1+0.090X2+0.172X3+?.